The Role of Islamic Banking in the Development of Economic Sectors in Indonesia - Iwan Setiawan (Politeknik Negeri Bandung, 2019)
Islamic bank can play a role in improving the welfare of the community. Through the intermediary function, Islamic banks raise funds deposits and channel financing for productive purposes. The purpose of this study is to examine the role of Islamic bank financing to increase economic productivity and job creation. This study uses simultaneous panel estimation technique with Two Stage Least Square (TSLS) method, using secondary data from 2005-2016. The results of this study reveal that the financing of Islamic banks play a role in increasing economic activity and employment, the role of Islamic banks finance large from the role of conventional bank credit, although the contribution is not too large. Regression result per sector of economy indicates that financing of syariah bank give positive role to increase economic activity in each. The role of financing for job creation by economic sector shows different results. Most Shariah banking financing in the economic sector (7 sectors) provides a positive role for job creation. Financing in the agricultural and mining sectors plays a negative role in job creation.